Solving Interoperability in Translational Health - Turner, Anne M.; Facelli, Julio C.; Jaspers, Monique; Wetter, Thomas; Pfeifer, Daniel; Gatewood, Laël Cranmer; Adam, Terry; Li, YuChuan; Lin, Ming-Chin; Evans, R. Scott; Beukenhorst, Anna; Theodoore van Mens, Hugo Johan; Tensen, Esmée; Bock, Christian; Fendrich, Laura; Seitz, Peter; Suleder, Julian; Aldekhyyel, Ranyah; Bridgeman, Kent; Hu, Zhen; Sattler, Aaron; Guo, Shin-Yi; Mohaimenul, Islam Md.; Anggraini Ningrum, Dina Nur; Tung, Hsin-Ru; Bian, Jiantao; Plasek, Joseph M.; Rommel, Casey; Burke, Juandalyn; Sohi, Harkirat (Applied Clinical Informatics, 2017)
Background: In the summer of 2016 an international group of biomedical and health informatics faculty and graduate students gathered for the 16th meeting of the International Partnership in Health Informatics Education (IPHIE) masterclass at the University of Utah campus in Salt Lake City, Utah. This international biomedical and health informatics workshop was created to share knowledge and explore issues in biomedical health informatics (BHI).Objective: The goal of this paper is to summarize the discussions of biomedical and health informatics graduate students who were asked to define interoperability, and make critical observations to gather insight on how to improve biomedical education.Methods: Students were assigned to one of four groups and asked to define interoperability and explore potential solutions to current problems of interoperability in health care.Results: We summarize here the student reports on the importance and possible solutions to the “interoperability problem” in biomedical informatics. Reports are provided from each of the four groups of highly qualified graduate students from leading BHI programs in the US, Europe and Asia.Conclusion: International workshops such as IPHIE provide a unique opportunity for graduate student learning and knowledge sharing. BHI faculty are encouraged to incorporate into their curriculum opportunities to exercise and strengthen student critical thinking to prepare our students for solving health informatics problems in the future.Citation: Turner AM, Facell JC, Jaspers M, Wetter T, Pfeifer D, Gatewood LC, Adam T, Li Y-C, Lin M-C, Evans RS, Beukenhorst A, van Mens H, Tensen E, Bock C, Fendrich L, Seitz P, Suleder J, Aldekhyyel R, Bridgeman K, Hu Z, Sattler A, Guo S-Y, Mohaimenul IMd, Ningrum DNA, Tung H-R, Bian J, Plasek JM, Rommel C, Burke J, Sohi H. Solving interoperability in translational health: perspectives of students from the International Partnership in Health Informatics Education (IPHIE) 2016 master class. Appl Clin Inform 2017; 8: 651–659 https://doi.org/10.4338/ACI-2017-01-CR-0012
Keywords: Clinical informatics; graduate education; interoperability; clinical data management; standards